A Structured Logit Model of Auto Ownership and Mode Choice - Train, Kenneth (Review of Economic Studies, 1980)
Journal Article A Structured Logit Model of Auto Ownership and Mode Choice Get access Kenneth Train Kenneth Train Cambridge Systematics Inc., Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 2, January 1980, Pages 357–370, https://doi.org/10.2307/2296997 Published: 01 January 1980 Article history Received: 01 April 1978 Accepted: 01 December 1978 Published: 01 January 1980